Implications for public access defibrillation placement by non‐traumatic out‐of‐hospital cardiac arrest occurrence in Singapore. (8th April 2014) - Zakaria, Nur Diana; Ong, Marcus Eng Hock; Gan, Han Nee; Foo, David; Doctor, Nausheen; Leong, Benjamin Sieu‐Hon; Goh, E Shaun; Ng, Yih Yng; Tham, Lai Peng; Charles, Rabind; Shahidah, Nur; Sultana, Papia; et al.
Abstract Introduction The American Heart Association recommends automated external defibrillator placement in public areas with a high probability (>1) of out‐of‐hospital cardiac arrest (OHCA) occurring in 5 years. We aimed to determine the incidence rate of OHCA for different location categories in Singapore. Methods Cardiac arrest incidence was obtained from a national registry. Denominators for the actual number of sites per location category were obtained from public accessible sources, government officers and purchased statistics. Analysis was performed and expressed in terms of the corresponding 95% confidence interval (CI). Results From 1 October 2001 to 14 October 2004, 2254 non‐trauma OHCA cases were included. Mean age for arrests was 62.2 years, with 67.5% men. The location category with the highest incidence of cardiac arrests per site per 5 years was Port/Airport/Immigration Checkpoints (5.24 CI [3.66–7.20]). Top individual site with high average incidence of cardiac arrests per 5 years was Changi Airport (25.0 CI [16.18–36.90]). Seventy‐one per cent of arrests occurred in residential areas. The postal sector with the highest average incidence per 100 000 population was Bedok Reservoir (54.89), whereas that with the highest population density was Bukit Merah/Alexandra with 348.14 population per 100 km2. Conclusion In this study, we found the categories and individual sites that clearly fulfilled the American Heart Association criteria of at least 1 OHCA per site per 5 years. This study provides a model of how cardiac arrest registry data can be used to guide local health policy on automated external defibrillator deployment.